Adhesive composition and film
By using components such as (meth)acrylic polymers in the adhesive, combined with specific crosslinking agents and antistatic agents, the problem of the existing UV peeling adhesive decreased after UV irradiation is solved, and the adhesion of existing UV peeling adhesives is achieved. Dual optimization of heat resistance and peeling performance in semiconductor processing.
Patent Information
- Application Number
- CN202410724012.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-05
- Publication Date
- 2024-12-31
AI Technical Summary
The adhesion of the existing UV peel adhesive decreases after UV irradiation, which cannot meet the dual requirements of heat resistance and peel performance in semiconductor processing, especially in fan-out wafer-level packaging process.
Adhesive compositions containing (meth)acrylic polymers, unsaturated double bond compounds with 4 functions or above, crosslinking agents, silane coupling agents, antistatic agents and photoinitiators are adopted to obtain specific composition ratios and treatments. In this way, an adhesive composition having excellent antistatic properties and heat resistance is formed.
On the basis of maintaining UV peeling performance, the heat resistance of the adhesive is improved, and it can be easily peeled off when necessary, meeting the requirements of the new manufacturing process, and avoiding a significant increase in the adhesive force in the heating process.
Smart Images

Figure CN119220185A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive composition and a film. Background Art
[0002] As adhesives used for semiconductor processing tapes, so-called UV peeling adhesives, represented by adhesives for dicing tapes, are generally known (for example, see Patent Document 1). The UV peeling adhesive has its adhesive strength reduced to 1N or less after UV irradiation, making it easy to peel.
[0003] Patent Document 1: Japanese Patent No. 6713864 Summary of the invention
[0004] As semiconductor processes have become more complex recently, the requirements for semiconductor processing tapes have become increasingly stringent. In particular, in the case of semiconductor processing tapes used in processes such as fan-out wafer-level packaging (FO-WLP) where ICs are directly placed on wafers, heat resistance during reflow processes is also required. In addition, in order to prevent damage to electronic components such as ICs, antistatic properties are sometimes required during the tape peeling process.
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an adhesive composition and a film sheet which can be suitably used as a UV peeling adhesive for semiconductor processing and which have excellent antistatic performance and heat resistance.
[0006] The first embodiment is an adhesive composition comprising a (meth)acrylic polymer, a tetrafunctional or higher unsaturated double bond compound, a crosslinking agent, (F) a silane coupling agent, (G) an antistatic agent, and (H) a photoinitiator, wherein the (meth)acrylic polymer is a copolymer comprising at least one (A) (meth)acrylic acid alkyl ester having an alkyl group with carbon atoms of C1 to C18 and a copolymerizable monomer without a carboxyl group and having a weight average molecular weight of 1,000,000 to 3,500,000, wherein the copolymerizable monomer without a carboxyl group is at least one (B) copolymerizable nitrogen-containing vinyl monomer and at least one (C) copolymerizable monomer containing a hydroxyl group, and the unsaturated double bond compound is selected from (D) a copolymer having at least four unsaturated double bonds in the molecule. The adhesive composition contains 0.1 to 10 parts by weight of the cross-linking agent, 0.1 to 3 parts by weight of the silane coupling agent (F), 0.5 to 30 parts by weight of the antistatic agent (G), and 0.1 to 5.0 parts by weight of the photoinitiator (H), relative to a total of 100 parts by weight of the (A) alkyl (meth)acrylate having an alkyl group with carbon atoms of C1 to C18 and the (B) copolymerizable nitrogen-containing vinyl monomer. The cross-linking agent is (E) a trifunctional or higher aromatic isocyanate compound, and the (G) antistatic agent is one or more ionic compounds having a melting point of 25° C. or higher.
[0007] The second embodiment is an adhesive composition according to the first embodiment, wherein the adhesive film formed by heating and drying the adhesive composition and stacking the adhesive layer with a thickness of 20 μm on a PEEK substrate with a thickness of 27 μm has a 90° peeling adhesion of 1 N / 25 mm or more to a silicon wafer treated with PBO, and then the silicon wafer with a diameter of 30.48 cm (12 inches) is subjected to UV irradiation at a ratio of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp, and then heated at 240°C for 5 minutes and further heated at 165°C for 2.5 hours. The adhesive strength after the test is 0.5 N / 25 mm or less, and the surface resistivity of the surface of the adhesive layer after peeling from the silicon wafer is 1.0×10 +10 Ω / □ or less, the 90° peeling adhesion of the adhesive film to the BA-treated stainless steel when subjected to the same test as the silicon wafer is 0.5 N / 25 mm or more, and the surface of the silicon wafer is not contaminated after peeling.
[0008] The third embodiment is: the adhesive composition according to the first embodiment or the second embodiment, wherein the (meth)acrylic polymer comprises at least one (A) alkyl (meth)acrylate having an alkyl group with carbon atoms of C1 to C18, at least one (B) copolymerizable nitrogen-containing vinyl monomer, and at least one (C) copolymerizable monomer containing a hydroxyl group, and in a total of 100 parts by weight of at least one (A) and (B), at least one (A) is 70 to 95 parts by weight, and (B) is 5 to 30 parts by weight, the (A) comprises at least 40 parts by weight of n-butyl acrylate, and the (B) is a nitrogen-containing vinyl monomer not containing a hydroxyl group.
[0009] A fourth embodiment is the adhesive composition according to any one of the first to third embodiments, wherein the (meth)acrylic polymer contains the (C) hydroxyl-containing copolymerizable monomer in an amount of 0.1 to 5 parts by weight relative to a total of 100 parts by weight of the (A) alkyl (meth)acrylate having an alkyl group with carbon atoms of C1 to C18 and the (B) copolymerizable nitrogen-containing vinyl monomer, and the (C) hydroxyl-containing copolymerizable monomer is one or more selected from hydroxyl-containing (meth)acrylates and hydroxyl-containing (meth)acrylamides.
[0010] The fifth embodiment is: the adhesive composition according to any one of the first to fourth embodiments, wherein the ionic compound having a melting point of 25°C or above as the antistatic agent (G) comprises 0.5 to 30 parts by weight of the following components: (G-1) is an ammonium ionic compound having a fluorine-containing anion, wherein the fluorine-containing anion is one selected from the group consisting of pentafluorobenzenesulfonate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and trifluoromethanesulfonate; (G-2) is a borate anion having a pentafluorophenyl group (C6F5 group); and a cation, the cation being one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidine, ammonium, isouronium, thioureonium, piperidinium, pyrazolium, methylium, lithium, and ammonium; and (G-3) an ionic compound consisting of a nonafluorobutane sulfonate anion and a cation, comprising one or more selected from the group consisting of the following components, the component being one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidine, ammonium, isouronium, thioureonium, piperidinium, pyrazolium, methylium, lithium, and ammonium.
[0011] A sixth embodiment is: the adhesive composition according to any one of the first to fifth embodiments, wherein the (C) hydroxyl-containing copolymerizable monomer is one or more selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.
[0012] A seventh embodiment is: the adhesive composition according to any one of the first to sixth embodiments, wherein the adhesive composition comprises 5 to 30 parts by weight of the (D) acrylate having 4 or more unsaturated double bonds in the molecule relative to a total of 100 parts by weight of the (A) alkyl (meth)acrylate having an alkyl group with carbon atoms of C1 to C18 and the (B) copolymerizable nitrogen-containing vinyl monomer, wherein the (D) acrylate having 4 or more unsaturated double bonds in the molecule is one or more acrylate compounds selected from the group consisting of pentaerythritol tetraacrylate, di(trihydroxymethyl)propane tetraacrylate, dipentaerythritol polyacrylate, and polypentaerythritol polyacrylate.
[0013] An eighth embodiment is the adhesive composition according to any one of the first to seventh embodiments, wherein the (E) tri- or higher-functional aromatic isocyanate compound is at least one selected from an adduct of toluene diisocyanate and an adduct of xylylene diisocyanate.
[0014] A ninth embodiment is the adhesive composition according to any one of the first to eighth embodiments, wherein the (F) silane coupling agent has at least one selected from the group consisting of epoxy groups, (meth)acryloyloxy groups, mercapto groups, amino groups, and polyether groups as organic functional groups.
[0015] A tenth aspect is a film sheet comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of the first to ninth aspects.
[0016] An eleventh embodiment is the film according to the tenth embodiment, wherein the substrate of the adhesive layer is a heat-resistant substrate having a thickness of 25 μm or more.
[0017] The twelfth embodiment is: the diaphragm according to the eleventh embodiment, wherein the heat-resistant substrate is selected from polyimide films, PEEK, PEN, polyamide films, and polystyrene films.
[0018] A thirteenth aspect is: the diaphragm according to any one of the tenth to twelfth aspects, wherein the diaphragm is used in a semiconductor processing step.
[0019] A fourteenth embodiment is: the diaphragm according to the thirteenth embodiment, wherein the diaphragm is used in a wafer-level packaging process as a semiconductor processing process.
[0020] According to the present invention, it is possible to provide an adhesive composition and a film sheet which can be suitably used as a UV peeling adhesive for semiconductor processing and which are excellent in both antistatic performance and heat resistance.
[0021] The adhesive composition of the present invention can be used as an adhesive that maintains heat resistance while maintaining the performance of conventional UV peeling adhesives, and can be easily peeled off even after a process requiring heat resistance. Conventional UV peeling adhesives have a significant increase in adhesive strength during the heating process after UV irradiation and cannot cope with new manufacturing processes, but in the present invention, by using an adhesive composition containing a (meth) acrylic polymer and other compounds of a specific composition, it is possible to have both UV peeling performance and heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a cross-sectional view showing an example of bonding a film sheet to an adherend.
[0023] (Explanation of Reference Numerals)
[0024] 10: Diaphragm
[0025] 11: Adhesive layer
[0026] 12: Base material
[0027] 20: Adhesive DETAILED DESCRIPTION
[0028] Hereinafter, the present invention will be described based on preferred embodiments.
[0029] The adhesive composition of the embodiment is an adhesive composition containing a (meth)acrylic polymer, a tetrafunctional or higher unsaturated double bond compound, a crosslinking agent, (F) a silane coupling agent, (G) an antistatic agent, and (H) a photoinitiator. The (meth)acrylic polymer contains one or more (A) (meth)acrylic acid alkyl esters having an alkyl group with carbon atoms of C1 to C18 and copolymerizable monomers without a carboxyl group, wherein the copolymerizable monomers without a carboxyl group are one or more (B) copolymerizable nitrogen-containing vinyl monomers and one or more (C) copolymerizable monomers containing a hydroxyl group.
[0030] The (meth)acrylic polymer may be a copolymer of one or more (A) (meth)acrylic acid alkyl esters having an alkyl group with carbon atoms of C1 to C18, one or more (B) copolymerizable nitrogen-containing vinyl monomers, and one or more (C) copolymerizable monomers containing a hydroxyl group, or may be a copolymer further containing monomers other than these monomers. The (meth)acrylic polymer is preferably copolymerized with only copolymerizable monomers not containing a carboxyl group.
[0031] (A) The (meth)acrylic acid alkyl ester having an alkyl group with carbon number of C1 to C18 and (B) the copolymerizable nitrogen-containing vinyl monomer are monomers containing no hydroxyl group and carboxyl group. In the following description, their total ratio may be referred to as "100 parts by weight of the total of (A) and (B)".
[0032] The (meth)acrylic acid alkyl ester having an alkyl group of C1 to C18 is not particularly limited and can be appropriately selected. Examples of the alkyl group of the (meth)acrylic acid alkyl ester monomer include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, n-octyl, isooctyl, 2-ethylhexyl, n-nonyl, isononyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, myristyl, stearyl, isomyristyl, isostearyl, cyclopentyl, and cyclohexyl.
[0033] In the present specification, (meth)acrylate may be any one of acrylate and / or methacrylate. For example, when the alkyl group is n-butyl, n-butyl (meth)acrylate may be any one of n-butyl acrylate and / or n-butyl methacrylate. The alkyl group of the (meth)acrylate alkyl ester monomer may be any one of acyclic (straight chain, branched chain) and cyclic.
[0034] The (meth)acrylic acid alkyl ester having an alkyl group with carbon numbers of C1 to C18 in the (meth)acrylic acid polymer may be one or two or more. The (meth)acrylic acid polymer preferably contains a total of one or more (meth)acrylic acid alkyl ester having an alkyl group with carbon numbers of C1 to C18 in a ratio of 70 to 95 parts by weight based on 100 parts by weight of (A) and (B).
[0035] The (meth)acrylic polymer preferably contains 40 parts by weight or more of n-butyl acrylate in 100 parts by weight of the total of (A) and (B). The proportion of n-butyl acrylate may be 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight, 95 parts by weight, etc. In the (meth)acrylic polymer, the (meth)acrylic alkyl ester having an alkyl group with carbon atoms of C1 to C18 in (A) may be only one type of n-butyl acrylate, or n-butyl acrylate and other (meth)acrylic alkyl esters may be used in combination.
[0036] In the (meth)acrylic polymer, the (B) copolymerizable nitrogen-containing vinyl monomer is a copolymerizable monomer having no carboxyl group and is different from the (C) copolymerizable monomer having a hydroxyl group. The (B) copolymerizable nitrogen-containing vinyl monomer is preferably a monofunctional unsaturated double bond compound.
[0037] The copolymerizable nitrogen-containing vinyl monomer (B) is not particularly limited, and examples thereof include N-vinyl-substituted lactams, N-vinyl-substituted cyclic amines, N-(meth)acryloyl-substituted cyclic amines, acrylic monomers containing N,N-dialkyl-substituted amino groups, acrylic monomers containing N,N-dialkyl-substituted amide groups, etc. In the present specification, the (meth)acryloyl group may be either an acryloyl group and / or a methacryloyl group.
[0038] Examples of the N-vinyl-substituted lactams include N-vinyl pyrrolidone, methyl vinyl pyrrolidone, and N-vinyl caprolactam.
[0039] Examples of the N-vinyl-substituted cyclic amines include N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, and N-vinylmorpholine.
[0040] Examples of the N-(meth)acryloyl-substituted cyclic amines include N-(meth)acryloylmorpholine, N-(meth)acryloylpiperazine, N-(meth)acryloylaziridine, N-(meth)acryloylpyrrolidine, and N-(meth)acryloylpiperidine.
[0041] Examples of acrylic monomers containing an N,N-dialkyl substituted amino group include dialkylamino substituted (meth) alkyl acrylates and dialkylamino substituted alkyl (meth) acrylamides. Examples of acrylic monomers containing an N,N-dialkyl substituted amide group include N,N-dialkyl substituted (meth) acrylamides. In the present specification, (meth) acrylamide may be any of acrylamide and / or methacrylamide.
[0042] Examples of the dialkylamino-substituted alkyl (meth)acrylate include N-ethyl-N-methylamino ethyl (meth)acrylate, N-methyl-N-propylamino ethyl (meth)acrylate, N-methyl-N-isopropylamino ethyl (meth)acrylate, N,N-dimethylamino methyl (meth)acrylate, N,N-dimethylamino ethyl (meth)acrylate, N,N-dimethylamino propyl (meth)acrylate, N,N-dimethylamino butyl (meth)acrylate, N,N-dipropylamino ethyl (meth)acrylate, and N,N-dibutylamino ethyl (meth)acrylate.
[0043] Examples of the dialkylamino-substituted alkyl (meth)acrylamide include N-ethyl-N-methylaminopropyl (meth)acrylamide, N-methyl-N-propylaminopropyl (meth)acrylamide, N-methyl-N-isopropylaminopropyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylamide, N,N-dipropylaminopropyl (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylamide, and N,N-diethylaminoethyl (meth)acrylamide. The dialkylamino-substituted alkyl group may be an N-substituent of the (meth)acrylamide compound.
[0044] Examples of the N,N-dialkyl-substituted (meth)acrylamide include N-ethyl-N-methyl (meth)acrylamide, N-methyl-N-propyl (meth)acrylamide, N-methyl-N-isopropyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, and N,N-dibutyl (meth)acrylamide.
[0045] The (B) copolymerizable nitrogen-containing vinyl monomer copolymerized in the (meth)acrylic polymer may be one type or two or more types. The (meth)acrylic polymer preferably contains one or more types of (B) copolymerizable nitrogen-containing vinyl monomers in a total amount of 5 to 30 parts by weight in 100 parts by weight of the total of (A) and (B).
[0046] In the (meth)acrylic polymer, the copolymerizable monomer (C) containing a hydroxyl group includes a (meth)acrylate containing a hydroxyl group, a (meth)acrylamide containing a hydroxyl group, etc. The copolymerizable monomer (C) containing a hydroxyl group is a monomer not containing a carboxyl group. The copolymerizable monomer (C) containing a hydroxyl group is preferably a monofunctional unsaturated double bond compound.
[0047] Examples of the hydroxyl group-containing (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate.
[0048] Examples of the (meth)acrylamide containing a hydroxyl group include N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.
[0049] The (C) hydroxyl group-containing copolymerizable monomer is preferably at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.
[0050] The (C) copolymerizable monomer containing a hydroxyl group copolymerized in the (meth)acrylic polymer may be one type or two or more types. The (meth)acrylic polymer preferably contains a total of 0.1 to 5 parts by weight of one or more (C) copolymerizable monomer containing a hydroxyl group relative to 100 parts by weight of the total of (A) and (B).
[0051] Similar to the carboxyl-containing monomer, the (C) hydroxyl-containing copolymerizable monomer can also react with the isocyanate compound of the crosslinking agent. Therefore, by using the (C) hydroxyl-containing copolymerizable monomer instead of the carboxyl-containing monomer, the adhesive force of the adhesive layer can be improved and the corrosiveness can be reduced. The acid value of the (meth)acrylic polymer can be 0.1 or less.
[0052] The polymerization method of the copolymer used as the (meth)acrylic polymer is not particularly limited, and known polymerization methods such as solution polymerization and emulsion polymerization can be appropriately used. The (meth)acrylic polymer preferably contains 50 wt % to 100 wt % of an acrylic monomer such as a (meth)acrylic ester monomer or a (meth)acrylamide monomer.
[0053] The weight average molecular weight of the (meth)acrylic polymer is preferably 1,000,000 to 3,500,000, and may be 1,500,000 or more.
[0054] The adhesive composition of the embodiment contains the (meth) acrylic polymer and a tetrafunctional or higher unsaturated double bond compound. The unsaturated double bond contained in the unsaturated double bond compound is preferably an unsaturated double bond between carbons that does not constitute an aromatic group. The unsaturated double bond may be contained in a (meth) acryloyl group of (meth) acrylate, (meth) acrylamide, etc., or may be a vinyl group, an allyl group, etc.
[0055] The unsaturated double bond compound is preferably one or more selected from (D) acrylates having 4 or more unsaturated double bonds in the molecule. Examples of the acrylates having 4 or more unsaturated double bonds in the molecule include acrylate compounds derived from polyol compounds having 4 or more hydroxyl groups in the molecule.
[0056] Examples of the polyol compound include pentaerythritol, dipentaerythritol, polypentaerythritol, di(trimethylol)propane, polytrimethylolpropane, etc. (D) Acrylate having 4 or more unsaturated double bonds in the molecule corresponds to a compound in which all or part of the hydroxyl groups contained in the polyol compound are converted into 4 or more acrylates.
[0057] The adhesive composition preferably contains 1 to 50 parts by weight of (D) an acrylate having 4 or more unsaturated double bonds in the molecule, relative to 100 parts by weight of the total of (A) and (B), and more preferably contains 5 to 30 parts by weight of (D) an acrylate having 4 or more unsaturated double bonds in the molecule. In addition, as (D) an acrylate having 4 or more unsaturated double bonds in the molecule, it is preferred to contain 5 to 30 parts by weight of one or more acrylate compounds selected from the group consisting of pentaerythritol tetraacrylate, di(trimethylol)propane tetraacrylate, dipentaerythritol polyacrylate, and polypentaerythritol polyacrylate.
[0058] The adhesive composition preferably contains (E) a trifunctional or higher-functional aromatic isocyanate compound as a crosslinking agent. Examples of the aromatic isocyanate compound include compounds derived from toluene diisocyanate (TDI), xylylene diisocyanate (XDI), diphenylmethane diisocyanate (MDI), and the like.
[0059] Examples of trifunctional or higher-functional isocyanate compounds include adducts, biuret forms, isocyanurate forms, etc. Examples of the adducts include adducts with trivalent or higher-valent polyols such as trimethylolpropane (TMP) and glycerol.
[0060] The (E) trifunctional or higher aromatic isocyanate compound is preferably one or more selected from the group consisting of an adduct of toluene diisocyanate and an adduct of xylylene diisocyanate. The adhesive composition preferably contains the (E) trifunctional or higher aromatic isocyanate compound in a ratio of 0.1 to 10 parts by weight relative to 100 parts by weight of the total of (A) and (B).
[0061] The adhesive composition contains (F) a silane coupling agent. The (F) silane coupling agent preferably has one or more organic functional groups selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, an amino group, and a polyether group. In addition, oligomerized alkoxy oligomers (silicone alkoxy oligomers) containing these organic functional groups can also be suitably used as the (F) silane coupling agent.
[0062] Examples of the silane coupling agent having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 5,6-epoxyhexyltrimethoxysilane, and 5,6-epoxyhexylmethyldimethoxysilane.
[0063] Examples of the silane coupling agent having a (meth)acryloyloxy group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylethoxysilane, and 3-(meth)acryloxypropyldimethylmethoxysilane.
[0064] Examples of the silane coupling agent having a mercapto group include 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, and 3-mercaptopropyltriethoxysilane.
[0065] Examples of the silane coupling agent having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-(methylamino)propyltrimethoxysilane, and 3-(methylamino)propyltriethoxysilane.
[0066] As a silane coupling agent having a polyether group, for example, a silane coupling agent having the general formula: R 1 -(OR 2 ) n -Si(OR 3 )3 represents a silane coupling agent containing a perfluoropolyether group. Here, R 1 is a perfluoroalkyl group such as C3F7. 2 They may be the same as or different from each other and may be perfluoroalkylene such as CF2, C2F4, C3F6 or alkylene such as CH2, C2H4, C3H6. 3 is an alkyl group such as methyl group or ethyl group. n is an integer greater than or equal to 1.
[0067] The adhesive composition preferably contains the silane coupling agent (F) in a ratio of 0.1 to 3 parts by weight based on 100 parts by weight of the total of (A) and (B).
[0068] The adhesive composition contains (G) an antistatic agent. The adhesive composition preferably contains (G) an antistatic agent in a ratio of 0.5 to 30 parts by weight based on 100 parts by weight of the total of (A) and (B).
[0069] The adhesive composition preferably contains one or more ionic compounds having a melting point of 25°C or higher as the (G) antistatic agent. As the (G) antistatic agent, an ionic compound having a melting point of 25°C or higher can be selected by selecting cations and / or anions from ionic compounds having cations and anions. By setting the melting point of the (G) antistatic agent to be 25°C or higher, the heat resistance of the antistatic agent can be maintained and the antistatic agent can be prevented from seeping out to the surface of the adhesive layer and contaminating the adherend.
[0070] As the cation of the antistatic agent (G), one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidine, ammonium, isourea, thiourea, piperidinium, pyrazolium, methylium, lithium, and ammonium can be cited. For these cations, except for the case where the cation is lithium, one or more substituents can be present. As the substituent of the cation, organic groups such as alkyl groups can be cited.
[0071] As the anion of the antistatic agent (G), inorganic or organic fluorine-containing anions can be cited. Here, the fluorine group refers to a fluorine atom bonded to other atoms constituting the anion. As inorganic fluorine-containing anions, PF6 - 、AsF6 - 、SbF6 - 、BF4 - 、AlF4 - 、(FSO2)2N - 、FSO3 -As organic fluorine-containing anions, sulfonate anions (RSO3 - ), carboxylate anions containing fluorine groups (RCOO - ), fluoride-containing alcohol or phenol anion (RO - ), organic imide anions containing fluorine groups (R2N - ), methylated anions containing fluorine groups (R3C - ), organic borate anions containing fluorine groups (R4B - ) etc. and having at least one anion as R of a fluorine-containing organic group.
[0072] As the organic group of R in the anion of the antistatic agent (G), one or more of an alkyl group, an alkoxy group, an aromatic group (aryl group, aralkyl group, etc.), an alkyl carbonyl group, an aromatic carbonyl group, an alkyl sulfonyl group, an aromatic sulfonyl group, etc. can be listed. When the anion has two or more Rs, a linking bond may be formed between the two or more Rs to form a ring.
[0073] The ionic compound having a melting point of 25° C. or higher as the antistatic agent (G) preferably contains 0.5 to 30 parts by weight of one or more ionic compounds selected from the group consisting of the following (G-1) to (G-3) based on 100 parts by weight of the total of (A) and (B).
[0074] As (G-1) an ammonium ionic compound having a fluorine-containing anion, there can be mentioned an ionic compound in which the fluorine-containing anion is one selected from the group consisting of pentafluorobenzenesulfonate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and trifluoromethanesulfonate. The ammonium ionic compound has ammonium as a cation. The substituent of ammonium may be a substituent not containing a fluorine group or a substituent containing a fluorine group.
[0075] As (G-2) an ionic compound composed of a borate anion having a pentafluorophenyl group (C6F5 group) and a cation, there can be mentioned an ionic compound in which the cation is one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidine, ammonium, isouronium, thioureonium, piperidinium, pyrazolium, methylonium, lithium, and ammonium. As the borate anion having a C6F5 group, it is sufficient that at least one of the four organic groups R is a C6F5 group. As a specific example, B(C6F5)4 - .
[0076] Examples of the ionic compound (G-3) composed of a nonafluorobutanesulfonate anion and a cation include an ionic compound in which the cation is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidine, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylonium, lithium and ammonium.
[0077] The adhesive composition contains (H) a photoinitiator. The (H) photoinitiator is not particularly limited, and examples thereof include acetophenone-based photoinitiators, benzoin-based photoinitiators, benzophenone-based photoinitiators, and thioxanthone-based photoinitiators.
[0078] Examples of the acetophenone-based photoinitiator include acetophenone, p-(tert-butyl)-1',1',1'-trichloroacetophenone, chloroacetophenone, 2',2'-diethoxyacetophenone, hydroxyacetophenone, 2,2-dimethoxy-2'-phenylacetophenone, 2-aminoacetophenone, dialkylaminoacetophenone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, and 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone.
[0079] As benzoin-based photoinitiators, benzil, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-2-methylpropane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, benzil dimethyl ketal, 2,2-dimethoxy-1,2-diphenylethane-1-one, etc.
[0080] Examples of the benzophenone-based photoinitiator include benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, methyl o-benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, hydroxypropylbenzophenone, acryloxybenzophenone, and 4,4′-bis(dimethylamino)benzophenone.
[0081] Examples of the thioxanthone-based photoinitiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, diethylthioxanthone, and dimethylthioxanthone.
[0082] As other photoinitiators, α-acyl oxime esters, benzyl-(o-ethoxycarbonyl)-α-monoxime, acylphosphine oxides, phenylglyoxylate, 3-coumarin ketone, 2-ethylanthraquinone, camphorquinone, tetramethylthiuram sulfide, azobisisobutyronitrile, benzoyl peroxide, dialkyl peroxide, tert-butyl peroxypivalate, etc. can be listed.
[0083] The adhesive composition preferably contains (H) a photoinitiator in a ratio of 0.1 to 5.0 parts by weight based on 100 parts by weight of the total of (A) and (B).
[0084] In addition to the above examples, the adhesive composition of the embodiment may also be appropriately formulated with known additives such as antioxidants, surfactants, hardening accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, hardening retarders, processing aids, anti-aging agents, antistatic agents, etc. as arbitrary components. These components may be used alone or in combination of two or more.
[0085] The adhesive film formed by the adhesive composition of the embodiment subjected to heat drying treatment preferably has a 90° peeling adhesion of 1N / 25mm or more to a silicon wafer treated with PBO. Here, PBO treatment refers to polybenzoxazole treatment. The adhesive film for testing the adhesive strength can be, for example, a film obtained by laminating an adhesive layer having a thickness of 20 μm on a PEEK substrate having a thickness of 27 μm. In addition, PEEK refers to polyetheretherketone resin.
[0086] For the adhesive film formed by further performing the above-mentioned heat drying treatment, after the heat drying treatment, the adherend (silicon wafer) with a diameter of 30.48 cm (12 inches) is subjected to UV irradiation at a ratio of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp (before the heat treatment of heating at 240°C × 5 minutes and further heating at 165°C × 2.5 hours described below) has a 90° peeling adhesive strength to the silicon wafer subjected to the PBO treatment of preferably 0.5 N / 25 mm or less. The adhesive strength is more preferably 0.3 N / 25 mm or less.
[0087] For the adhesive film formed by further performing the above-mentioned heat drying treatment, after the heat drying treatment, a 30.48 cm (12 inch) diameter adherend (silicon wafer) is subjected to UV irradiation at a ratio of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp, and then heated at 240°C for 5 minutes and further heated at 165°C for 2.5 hours. The 90° peeling adhesive force to the silicon wafer subjected to the PBO treatment is preferably 0.5 N / 25 mm or less. The adhesive force is more preferably 0.3 N / 25 mm or less.
[0088] In addition, the same test is conducted, and the adhesive film formed by the above-mentioned heat drying treatment is subjected to UV irradiation at a ratio of 3000mJ on an adherend (stainless steel treated with BA) with a diameter of 30.48cm (12 inches) using a metal halide lamp or a 365nm wavelength LED-UV lamp after the heat drying treatment, and then heated at 240°C for 5 minutes and further heated at 165°C for 2.5 hours. After the test, the 90° peeling adhesive strength to the stainless steel treated with BA is preferably 0.5N / 25mm or more. Here, BA treatment refers to bright annealing treatment.
[0089] The surface resistivity of the adhesive layer after peeling from the silicon wafer is preferably 1.0×10 +10 Ω / □ or less. This can suppress the peeling static electricity of the adhesive film and the adherend. The silicon wafer used in the measurement of the surface resistivity can be the same as the adherend (PBO-treated silicon wafer) used in the measurement of the adhesive strength.
[0090] The adhesive film preferably does not contaminate the surface of the silicon wafer after peeling. This can prevent the surface of the silicon wafer or the like that becomes the adherend from being contaminated.
[0091] The adhesive layer composed of the adhesive composition of the embodiment can be used for a film. Figure 1 2 shows an example in which the adhesive layer 11 of the film sheet 10 is bonded to the adherend 20. The film sheet 10 preferably has the adhesive layer 11 on one surface of the substrate 12.
[0092] The substrate 12 is preferably a heat-resistant substrate having a thickness of 25 μm or more. The heat-resistant substrate is preferably selected from polyimide films, polyetheretherketone (PEEK), polyethylene naphthalate (PEN), polyamide films, and polystyrene films.
[0093] It is preferable to select a material with high heat resistance to meet the requirements of semiconductor processing steps as the substrate 12. Examples of polyamide films and polystyrene films include aromatic polyamide and syndiotactic polystyrene (SPS) which have higher heat resistance than general-purpose resins (nylon, general-purpose polystyrene).
[0094] The film 10 can be used in semiconductor processing steps such as wafer level packaging (WLP) steps. The adhesive layer 11 is preferably bonded to the adherend 20 in a state where the (meth)acrylic polymer contained in the adhesive composition is crosslinked using (E) a trifunctional or higher aromatic isocyanate compound as a crosslinking agent.
[0095] Furthermore, it is preferable that the adhesion of the membrane 10 to the silicon wafer is reduced by ultraviolet (UV) irradiation. Also, it is preferable that the adhesion to stainless steel is maintained at a predetermined level or higher even after ultraviolet (UV) irradiation.
[0096] Before the film sheet 10 is attached to the adherend 20, a release film (spacer) may be used to protect the adhesive surface of the adhesive layer 11. As the release film, a resin film such as a polyester film may be used. The release film may be a release film treated with a release agent, a coating agent, an antifouling treatment, or an antistatic treatment.
[0097] The present invention has been described above based on preferred embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the scope of the gist of the present invention. As changes, addition, replacement, omission, and other changes of the components in each embodiment can be listed.
[0098] [Example]
[0099] Hereinafter, the present invention will be specifically described based on examples.
[0100] <Manufacturing of acrylic polymer>
[0101] Nitrogen was introduced into a reaction device equipped with a stirrer, a thermometer, a reflux cooler and a nitrogen introduction tube, and the air in the reaction device was replaced with nitrogen. Then, the monomers shown in Table 1 were added so that the total of (A) and (B) was 100 parts by weight, and 60 parts by weight of a solvent (ethyl acetate) were added. Then, 0.1 parts by weight of azobisisobutyronitrile was added dropwise as a photoinitiator over 2 hours, and the reaction was carried out at 65° C. for 6 hours to obtain an acrylic polymer solution. The weight average molecular weight (Mw) of the acrylic polymer is shown in Table 1.
[0102]
Table 1
[0103]
[0104] The meanings of the abbreviations used in Table 1 (compound names, etc.) are as follows. In Table 1, the numerical values following these abbreviations are parts by weight relative to 100 parts by weight of the total of (A) and (B).
[0105] In Table 1, as group (A), n-butyl acrylate (BA), ethyl acrylate (EA), 2-ethylhexyl acrylate (2EHA), methyl acrylate (MA), isooctyl acrylate (IOA), isobutyl acrylate (IBA), and n-butyl methacrylate (BMA) were used.
[0106] In addition, as group (B), N-vinylpyrrolidone (NVP), N,N-diethylacrylamide (DEAA), N,N-dimethylacrylamide (DMAA), N,N-diisopropylacrylamide (DIPAA), and N-[3-(dimethylamino)propyl]methacrylamide (DMAPMA) were used.
[0107] In addition, as group (C), 8-hydroxyoctyl acrylate (8HOA), 6-hydroxyhexyl acrylate (6HHA), 4-hydroxybutyl acrylate (4HBA), 2-hydroxyethyl acrylate (HEA), N-hydroxymethyl acrylamide (HMAA), and N-hydroxyethyl acrylamide (HEAA) were used.
[0108] In addition, the (X) group is a carboxyl group-containing monomer, and in Comparative Example 4, acrylic acid (AAc) was used.
[0109] <Manufacturing of Adhesive Composition and Adhesive Layer>
[0110] The additives shown in Table 2 were added to the acrylic polymer solution, and the mixture was stirred and mixed to obtain an adhesive composition. The adhesive composition was applied to a release film composed of a polyethylene terephthalate (PET) film coated with a silicone resin, and then dried at 90° C. to remove the solvent, and then aged for 7 days in an atmosphere of 23° C. and 50% RH to obtain an adhesive layer. The adhesive film for the adhesive strength test can laminate an adhesive layer having a thickness of 20 μm on a PEEK substrate having a thickness of 27 μm.
[0111]
Table 2
[0112]
[0113] The meanings of the abbreviations used in Table 2 (compound names, etc.) are as follows. In Table 2, the numerical values following these abbreviations are parts by weight relative to 100 parts by weight of the total of (A) and (B).
[0114] In Table 2, as group (D), tetrafunctional pentaerythritol tetraacrylate (D-1), hexafunctional or higher-functional polypentaerythritol polyacrylate (D-2), tetrafunctional di(trihydroxymethyl)propane tetraacrylate (D-3), hexafunctional dipentaerythritol hexaacrylate (D-4), bifunctional 1,6-hexanediol diacrylate (D-5), and trifunctional pentaerythritol triacrylate (D-6) were used.
[0115] In addition, as group (E), Takenate (registered trademark) D-101, Takenate (registered trademark) D-110N, and Coronate (registered trademark) HL were used. "D-101" is a trimethylolpropane (TMP) adduct of toluene diisocyanate (TDI), "D-110N" is a trimethylolpropane (TMP) adduct of xylylene diisocyanate (XDI), and "HL" is an adduct of hexamethylene diisocyanate (HDI).
[0116] In addition, as the (F) group, a silane coupling agent having an epoxy group (trade name: X-24-9590) was used as "F-1", a silane coupling agent having a mercapto group (trade name: X-12-1154) was used as "F-2", and a silane coupling agent having an acryloxy group (trade name: KBM-503) was used as "F-3".
[0117] In addition, as the (G) group, tetrabutylammonium trifluoromethanesulfonate (melting point 113°C) was used as "G-1-1", methyltri-n-butylammonium bis(trifluoromethanesulfonyl)imide (melting point 27°C) was used as "G-1-2", trimethylhexylammonium bis(trifluoromethanesulfonyl)imide (melting point 27°C) was used as "G-1-3", 4-methyl-1-hexylpyridinium bis(trifluoromethanesulfonyl)imide (melting point less than 25°C) was used as "G-1-4", and triphenylmethylium tetrakis(pentafluorophenyl)borate (melting point 183°C) was used as "G-1-5". As "G-2-1", (methoxymethyl)triphenylphosphonium tetrakis(pentafluorophenyl)borate (melting point 149°C) was used as "G-2-2", 1-ethyl-3-methylimidazolium tetrafluoroborate (melting point 15°C) was used as "G-2-3", lithium nonafluorobutane sulfonate (melting point 370°C) was used as "G-3-1", 4-methyl-1-octylpyridinium nonafluorobutane sulfonate (melting point 62°C) was used as "G-3-2", and 3-methyl-1-octylpyridinium nonafluorobutane sulfonate (melting point 41°C) was used as "G-3-3".
[0118] In addition, as the (H) group, OMNIRAD (registered trademark) 184 of the alkyl phenone type was used as "H-1", OMNIRAD (registered trademark) 369 of the alkyl phenone type was used as "H-2", IRGACURE (registered trademark) OXE01 of the oxime ester type was used as "H-3", and OMNIRAD (registered trademark) TPO of the acylphosphine oxide type was used as "H-4".
[0119] <Manufacturing of Diaphragms>
[0120] Film sheets were produced by transferring the adhesive layer formed on the release film onto the heat-resistant substrate shown in Table 3. The heat-resistant substrate was made of polyetheretherketone (PEEK), polyethylene naphthalate (PEN), polyamide (PA) film, and polystyrene (PS) film.
[0121] The initial adhesive strength shown in Table 3 was measured as 90° peeling adhesive strength after laminating the adhesive layer of the film to the PBO-treated wafer. The adhesive strength in Table 3 is indicated as "initial".
[0122] Regarding the adhesive strength after UV irradiation shown in Table 3, after the adhesive layer of the film was attached to the PBO-treated wafer, a metal halide lamp or a 365nm wavelength LED-UV lamp was used to irradiate the adherend with UV at a ratio of 3000mJ to a diameter of 30.48cm (12 inches), and then the 90° peeling adhesive strength was measured. In the adhesive strength of Table 3, it is indicated as "UV".
[0123] Regarding the adhesive strength after UV irradiation and heating shown in Table 3, after laminating the adhesive layer of the film on the adherend selected from the wafer treated with PBO or the stainless steel (SUS) treated with BA, the adherend with a diameter of 30.48 cm (12 inches) was UV irradiated at a ratio of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp, and further heated at 240°C for 5 minutes, and further heated at 165°C for 2.5 hours, and then measured as 90° peel adhesive strength. In the adhesive strength of Table 3, it is expressed as "UV+heating".
[0124]
Table 3
[0125]
[0126] Regarding the reprocessability shown in Table 3, the case where the adhesion of the film after UV irradiation and heating is less than 0.3N / 25mm is rated as good (○), the case where it is greater than 0.3N / 25mm and less than 3N / 25mm is rated as acceptable (△), and the case where it is greater than 3N / 25mm is rated as unacceptable (×).
[0127] The surface resistivity shown in Table 3 was measured using a resistivity meter on the adhesive layer after it was peeled off from the adherend (wafer treated with PBO). +n ” is expressed as “mE+n” (where m and n are positive real numbers).
[0128] Regarding the contamination resistance shown in Table 3, after measuring the adhesive strength of the film after UV irradiation and heating, it was visually confirmed whether the adhesive component was transferred to the surface of the adherend (wafer treated with PBO) and contaminated. The case where there was no contamination on the adherend at all was rated as good (○), the case where there was little contamination on a part or the whole of the adherend was rated as acceptable (△), and the case where there was contamination on the entire surface was rated as unacceptable (×).
[0129] In the films of Examples 1 to 9, (1) the initial adhesive force to the wafer treated with PBO was 1 N / 25 mm or more, (2) the adhesive force to the wafer treated with PBO after UV irradiation was 0.3 N / 25 mm or less, (3) the adhesive force to the wafer treated with PBO after UV irradiation and heating was 0.5 N / 25 mm or less, and (4) the adhesive force to the SUS treated with BA after UV irradiation and heating was 0.5 N / 25 mm or more. Furthermore, the films of Examples 1 to 9 have excellent antistatic performance and anti-fouling properties.
[0130] None of the film sheets of Comparative Examples 1 to 9 fully satisfied the requirements of (1), (3) and (4) described above. Furthermore, the film sheets of Comparative Examples 1 to 9 were also inferior in antistatic performance and antifouling properties.
[0131] In Comparative Example 1, the unsaturated double bond compound is a bifunctional acrylate, and the adhesive composition does not contain (G) an antistatic agent.
[0132] In Comparative Example 2, the Mw of the (meth)acrylic polymer was 480,000, and the pressure-sensitive adhesive composition did not contain the (G) antistatic agent.
[0133] In Comparative Example 3, (B) the copolymerizable nitrogen-containing vinyl monomer is not copolymerized with the (meth)acrylic polymer, and the melting point of (G) the antistatic agent is low.
[0134] In Comparative Example 4, the (C) hydroxyl group-containing copolymerizable monomer was not copolymerized with the (meth)acrylic polymer, and the pressure-sensitive adhesive composition did not contain the (G) antistatic agent.
[0135] In Comparative Example 5, the adhesive composition does not contain the (F) silane coupling agent, and the (G) antistatic agent has a low melting point.
[0136] In Comparative Example 6, the unsaturated double bond compound is a trifunctional acrylate, and the adhesive composition does not contain (G) an antistatic agent.
[0137] In Comparative Example 7, the crosslinking agent was an aliphatic isocyanate compound, and the proportion of the (G) antistatic agent was too small.
[0138] In Comparative Example 8, the adhesive composition does not include the (G) antistatic agent and the (H) photoinitiator.
[0139] In Comparative Example 9, the adhesive composition did not include the (G) antistatic agent.
Claims
1. An adhesive composition, characterized in that The adhesive composition contains a (meth)acrylic polymer, a tetrafunctional or higher unsaturated double bond compound, a crosslinking agent, (F) a silane coupling agent, (G) an antistatic agent, and (H) a photoinitiator. The (meth)acrylic polymer is a copolymer comprising one or more (A) (meth)acrylic acid alkyl esters having an alkyl group with carbon atoms of C1 to C18 and a copolymerizable monomer without a carboxyl group and having a weight average molecular weight of 1,000,000 to 3,500,000, wherein the copolymerizable monomer without a carboxyl group is one or more (B) copolymerizable nitrogen-containing vinyl monomers and one or more (C) copolymerizable monomers containing a hydroxyl group. The unsaturated double bond compound is one or more selected from (D) acrylic acid esters having 4 or more unsaturated double bonds in the molecule, The adhesive composition contains 0.1 to 10 parts by weight of the crosslinking agent, 0.1 to 3 parts by weight of the silane coupling agent, 0.5 to 30 parts by weight of the antistatic agent, and 0.1 to 5.0 parts by weight of the photoinitiator, relative to a total of 100 parts by weight of the (A) alkyl (meth)acrylate having an alkyl group with carbon atoms ranging from C1 to C18 and the (B) copolymerizable nitrogen-containing vinyl monomer. The crosslinking agent is (E) a trifunctional or higher aromatic isocyanate compound, and the (G) antistatic agent is one or more ionic compounds having a melting point of 25° C. or higher.
2. The adhesive composition according to claim 1, characterized in that The adhesive film obtained by laminating a 20 μm thick adhesive layer formed by heat-drying the adhesive composition on a 27 μm thick PEEK substrate has a 90° peeling adhesive force of 1 N / 25 mm or more to a PBO-treated silicon wafer. The silicon wafer having a diameter of 30.48 cm was then irradiated with UV at a rate of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp, and then heated at 240° C. for 5 minutes and further heated at 165° C. for 2.5 hours. The adhesive force after the test was 0.5 N / 25 mm or less. The surface resistivity of the adhesive layer after peeling off from the silicon wafer was 1.0×10 +10 Ω / □ or less, The 90° peeling adhesion of the adhesive film to the BA-treated stainless steel when subjected to the same test as the silicon wafer is 0.5 N / 25 mm or more. The surface of the silicon wafer after peeling is not contaminated.
3. The adhesive composition according to claim 1 or 2, characterized in that The (meth)acrylic polymer comprises at least one (A) alkyl (meth)acrylate whose alkyl group has carbon atoms of C1 to C18, at least one (B) copolymerizable nitrogen-containing vinyl monomer, and at least one (C) copolymerizable monomer containing a hydroxyl group, wherein in a total of 100 parts by weight of at least one (A) and (B), at least one (A) is 70 to 95 parts by weight, and at least one (B) is 5 to 30 parts by weight, the (A) comprises at least 40 parts by weight of n-butyl acrylate, and the (B) is a nitrogen-containing vinyl monomer containing no hydroxyl group.
4. The adhesive composition according to claim 1 or 2, characterized in that: The (meth)acrylic polymer contains the (C) hydroxyl-containing copolymerizable monomer in an amount of 0.1 to 5 parts by weight relative to a total of 100 parts by weight of the (A) alkyl (meth)acrylate having an alkyl group with carbon atoms ranging from C1 to C18 and the (B) copolymerizable nitrogen-containing vinyl monomer, wherein the (C) hydroxyl-containing copolymerizable monomer is one or more selected from hydroxyl-containing (meth)acrylates and hydroxyl-containing (meth)acrylamides.
5. The adhesive composition according to claim 1 or 2, characterized in that: The ionic compound having a melting point of 25° C. or higher as the antistatic agent (G) comprises 0.5 to 30 parts by weight of the following components: (G-1) is an ammonium ionic compound having a fluorine-containing anion, wherein the fluorine-containing anion is one selected from the group consisting of pentafluorobenzenesulfonate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and trifluoromethanesulfonate; (G-2) is an ionic compound composed of a borate anion having a pentafluorophenyl group and a cation, wherein the cation is one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidine, ammonium, isouronium, thioureonium, piperidinium, pyrazolium, methylonium, lithium, and ammonium; and (G-3) is an ionic compound composed of a nonafluorobutane sulfonate anion and a cation, wherein the cation contains one or more selected from the group consisting of ionic compounds consisting of the following components, wherein the component is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidine, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylonium, lithium, and ammonium.
6. The adhesive composition according to claim 1 or 2, characterized in that: The (C) hydroxyl-containing copolymerizable monomer is one or more selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.
7. The adhesive composition according to claim 1 or 2, characterized in that: The adhesive composition comprises 5 to 30 parts by weight of (D) an acrylate having 4 or more unsaturated double bonds in the molecule, relative to a total of 100 parts by weight of the (A) alkyl (meth)acrylate having an alkyl group with carbon atoms of C1 to C18 and the (B) copolymerizable nitrogen-containing vinyl monomer, wherein the (D) acrylate having 4 or more unsaturated double bonds in the molecule is one or more acrylate compounds selected from the group consisting of pentaerythritol tetraacrylate, di(trimethylol)propane tetraacrylate, dipentaerythritol polyacrylate, and polypentaerythritol polyacrylate.
8. The adhesive composition according to claim 1 or 2, characterized in that: The (E) tri- or higher-functional aromatic isocyanate compound is at least one selected from the group consisting of an adduct of tolylene diisocyanate and an adduct of xylylene diisocyanate.
9. The adhesive composition according to claim 1 or 2, characterized in that: The (F) silane coupling agent has at least one selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, an amino group, and a polyether group as an organic functional group.
10. A diaphragm, characterized in that: The film has an adhesive layer formed from the adhesive composition according to claim 1 or 2.
11. The diaphragm according to claim 10, characterized in that The substrate of the adhesive layer is a heat-resistant substrate with a thickness of 25 μm or more.
12. The diaphragm according to claim 11, characterized in that The heat-resistant substrate is selected from polyimide films, PEEK, PEN, polyamide films, and polystyrene films.
13. The diaphragm according to claim 10, characterized in that The diaphragm is used in semiconductor processing steps.
14. The diaphragm according to claim 13, characterized in that The diaphragm is used in a wafer-level packaging process as the semiconductor processing process.